DIAGNOSTIC VALUE OF KNEE ULTRA-SOUND EXAMINATION IN PATIENTS WITH SWELLING OF THE POPLITEAL FOSSA - Іваницький, І.В.; Пономаренко, С.О. (World of Medicine and Biology, 2014)
The article presents data on the differential diagnosis of swelling of the popliteal fossa, described the disease, which can occur with this symptom, clinical and ultrasound criteria necessary for the correct diagnosis. We developed an algorithm to determine the feasibility of ultrasound joint, which consists of the following: the presence of joint disease in history - 2 points, the presence of a history of injuries is estimated at 5 points , the lack of these symptoms - 7 points. Evaluation is carried out in pain intensity according to the number of points from 1 to 10 , the rate of development of pain is estimated as follows: instant - 6 points, quickly - 4 points, gradually - 2 points . Sample with clenching swelling, if it is positive , estimated at 2 points, if negative - 4 points. Based on these results we concluded on the need to perform ultrasound knee immediately if the amount was more than 15 points , according to plan, if the sum of scores ranged from 10 to 15, and the patient does not need an ultrasound of the knee, if the amount is less than 10 points. The developed algorithm may be used to determine the planning of ultrasound examination of the knee joint in each case.
Keywords: knee; Baker's cyst; bursitis; popliteal vein thrombosis; the diagnostic algorithm